A curta-metragem como recurso didático na aula de PLE: duas propostas didáticas - Matos, Catarina Raposo Santos de (2023)
This article presents a case study developed with the purpose of investigating the relevance of using short films as educational material for teaching Portuguese as a Foreign Language. The study was conducted with an A2 level class, of the Annual Course of Portuguese for Foreigners for the academic year 2016-2017, during the Pedagogical Internship undertaken within the scope of the Master in Portuguese as Second Language/Foreign Language, Faculty of Arts and Humanities, University of Porto. Considering the State of the Art together with the analysis of the intervention context, two educational proposals using short films were planned and implemented, following the methodological principles of Task-based Language Teaching. Data was then collected and analyzed. The results obtained confirmed the wide possibilities of using short films for the design of motivational activities aimed at different syllabus content thus providing a relevant tool for the integrated practice of primary language activities and for the development of the different communication skills.